Fenomena Standar Tiktok Dalam Pernikahan: Telaah Hadis Nabi Tentang Kriteria Memilih Pasangan Ideal - Nurhakim, Amien (Jurnal sosial dan sains, 2025)
This article discusses the phenomenon of “TikTok Standards” in the context of marriage and how the perspective of hadith can provide relevant guidance. With time, the standards for determining a partner have undergone significant shifts, and social media often creates unrealistic expectations regarding life partners. Through the analysis of hadith that emphasizes the importance of character and religious quality, this article demonstrates that the values essential in choosing a partner can lead individuals to make wiser and more sustainable decisions in their marital lives.